Two Family B DNA Polymerases From Aeropyrum pernix, Based on Revised Translational Frames - Daimon, Katsuya; Ishino, Sonoko; Imai, Namiko; Nagumo, Sachiyo; Yamagami, Takeshi; Matsukawa, Hiroaki; Ishino, Yoshizumi (Frontiers in Molecular Biosciences, 2018)
Abstract Living organisms are divided into three domains, Bacteria, Eukarya, and Archaea. Comparative studies in the three domains have provided useful information to understand the evolution of the DNA replication machinery. DNA polymerase is the central enzyme of DNA replication. The presence of multiple family B DNA polymerases is unique in Crenarchaeota, as compared with other archaeal phyla, which have a single enzyme each for family B (PolB) and family D (PolD). We analyzed PolB1 and PolB3 in the hyperthermophilic crenarchaeon, Aeropyrum pernix, and found that they are larger proteins than those predicted from the coding regions in our previous study and from public database annotations. The recombinant larger PolBs exhibited the same DNA polymerase activities as previously reported. However, the larger PolB3 showed remarkably higher thermostability, which made this enzyme applicable to PCR. In addition, the high tolerance to salt and heparin suggests that PolB3 will be useful for amplification from the samples with contaminants, and therefore it has a great potential for diagnostic use in the medical and environmental field.